PEMBUATAN SPESIMEN UJI LELAH TIPE CONTINUOUS RADIUS MENGGUNAKAN MESIN BUBUT CNC - Suprihanto, Agus; Wibowo, Dwi Basuki; Puja, IGN Wiratmaja (ROTASI, 2006)
Ones of considerations of design are fatigue failures. The fatigue failures are related with fatigue strength ofspecimens. The fatigue strength of materials usually resulted by fatigue testing. The results of the testing are influencedby some factors ie. machining process of specimens.The goal of this research is to give a proposed machining process of fatigue test specimens with CNC lathemachines. The proposed machining process can be eliminated the effects of machining from fatigue testing result.One examples of CNC lathe programming have been sucessfuly composed for fatigue test specimens typecontinuous radius. This specimen has 9,3mm minor diameter and 16mm major diameter. G and M code which used areG00, G~1, G02, M92, M99 and M30.